Proceedings of 16th Asian Congress of Fluid Mechanics - Venkatakrishnan, L.; Majumdar, Sekhar; Subramanian, Ganesh; Bhat, G. S.; Dasgupta, Ratul; Arakeri, Jaywant
This book includes select papers presented during the 16th Asian Congress of Fluid Mechanics, held in JNCASR, Bangalore, and presents the latest developments in computational, experimental and theoretical research as well as industrial and technological advances. This book is of interest to researchers working in the field of fluid mechanics.